2014
DOI: 10.5152/iao.2014.31
|View full text |Cite
|
Sign up to set email alerts
|

Venous Engorgement as a Cause of Facial Canal Enlargement

Abstract: There are various causes of facial canal enlargement. From congenital anomalies to neoplasms, many pathologic conditions should be considered. However, normal variants of vascular anatomy can also result in facial canal enlargement on temporal bone imaging. In order to avoid unnecessary procedures and complications, such as bleeding and facial nerve injury, this possibility should also be taken into account. A case of a 50-year-old male who was diagnosed with facial canal enlargement because of venous engorgem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
1
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 9 publications
2
1
0
Order By: Relevance
“…In those studies, the relevance of the venous anomaly to the embryonic primary head sinus remains unclear. We found three reports describing a dilated vein in the facial canal; 5,21,22) these cases were similar to the present Case 3. Nagar et al 22) reported on a case with a dilated vein situated in the facial canal from the genu to the stylomastoid foramen and asserted that the vein was the remnant of the lateral capital vein.…”
Section: Discussionsupporting
confidence: 87%
“…In those studies, the relevance of the venous anomaly to the embryonic primary head sinus remains unclear. We found three reports describing a dilated vein in the facial canal; 5,21,22) these cases were similar to the present Case 3. Nagar et al 22) reported on a case with a dilated vein situated in the facial canal from the genu to the stylomastoid foramen and asserted that the vein was the remnant of the lateral capital vein.…”
Section: Discussionsupporting
confidence: 87%
“…A venous cause for facial canal enlargement has been nicely described on both histopathology and CT by Moonis et al [2]. In another case report by Kim et al, in which similar findings on MR to our case were described, venous engorgement around the facial nerve was observed intraoperatively [3]. In these cases, there was no PSA.…”
Section: Discussionsupporting
confidence: 84%
“…This is confirmed by the prominent contrast enhancement around a normal facial nerve on MR imaging (Figure 1B). On the basis of literature data, we can confidently suppose that a vein rather than an artery causes the canal enlargement [2,3].…”
Section: Discussionmentioning
confidence: 92%